World Café between research and teaching: Individual and community empowerment - Nadia Rania; Arianna Marci; Ilaria Coppola (Encyclopaideia)
This article aims to describe, from both theoretical and methodological perspectives, the characteristics of the World Café as a participatory technique particularly flexible to the context in which it is employed, thanks to its ability to create informal and relaxed settings as opportunities to generate and share knowledge. The authors trace its origins and guiding principles, explore its possibilities of application — both in-person  and online settings —, highlighting its strengths and weaknesses in the fields of research, teaching and education, as a methodology capable of promoting and fostering empowerment, soft skills and social change among participants.